Cyanophage MazG is a pyrophosphohydrolase but unable to hydrolyse magic spot nucleotides. Issue 3 (20th March 2019) - Rihtman, Branko; Bowman‐Grahl, Sabine; Millard, Andrew; Corrigan, Rebecca M.; Clokie, Martha R. J.; Scanlan, David J.
Summary: Bacteriophage possess a variety of auxiliary metabolic genes of bacterial origin. These proteins enable them to maximize infection efficiency, subverting bacterial metabolic processes for the purpose of viral genome replication and synthesis of the next generation of virion progeny. Here, we examined the enzymatic activity of a cyanophage MazG protein – a putative pyrophosphohydrolase previously implicated in regulation of the stringent response via reducing levels of the central alarmone molecule (p)ppGpp. We demonstrate, however, that the purified viral MazG shows no binding or hydrolysis activity against (p)ppGpp. Instead, dGTP and dCTP appear to be the preferred substrates of this protein, consistent with a role preferentially hydrolysing deoxyribonucleotides from the high GC content host Synechococcus genome. This showcases a new example of the fine‐tuned nature of viral metabolic processes.